The Role of Internal Audit in Fraud Prevention and Financial Mismanagement in Local Governments in Indonesia - Raden Nasution; Emanuel M Bayudhirgantara; Dailibas Dailibas; Chaerudin Chaerudin (UIN Sunan Gunung Djati, 2025)
This study aims to analyze the role of internal audit in strengthening local government resilience against fraud and financial misconduct. The focus of the study is on the efforts of internal audit in detecting and preventing fraud, addressing resource limitations, and leveraging audit technology to improve oversight effectiveness. This research uses a qualitative approach with a case study method. Data were collected through in-depth interviews with 15 internal auditors from various government agencies, direct observations of audit practices, and document analysis. Data analysis was conducted inductively using data reduction, presentation, and conclusion drawing techniques, as well as validation through source triangulation. The findings of the study reveal three key conclusions. First, internal audit functions as a preventive and early detection mechanism through strengthening internal control systems and educating personnel. Second, resource limitations, both in terms of budget and the number and competence of auditors, have weakened audit effectiveness, resulting in some fraud going undetected. Third, the use of technology has the potential to increase audit efficiency and accuracy; however, its adoption is still hindered by limited infrastructure, low technical capacity, and resistance from senior auditors. The implications of this study emphasize the need to strengthen internal audit through improving human resource capacity, adequate budget allocation, legal protection for auditors, and the modernization of technology-based audit systems. This study provides an original contribution by offering a holistic approach that combines human, institutional, and technological aspects in analyzing the effectiveness of internal audits in local governments. Thus, this research enhances academic understanding and provides practical recommendations for public financial governance policies that are more transparent and accountable.